F-MARC: the FIFA Sudden Death Registry (FIFA-SDR) - Scharhag, J.; Bohm, P.; Dvorak, J.; Meyer, T. (British Journal of Sports Medicine, 2015)
Death of an athlete during sports is tragic, and sudden cardiac death (SCD) is the most common cause. It is estimated, that the incidence of a SCD in athletes varies between 1:917 000 and 1:3000, whereas studies with higher methodological quality consistently report ranges between 1:40 000 to 1:80 000. In addition, it has been stated that subgroups and sport disciplines may be at a higher risk for SCD, such as males, African-Americans, Africans/Americans, basketball, football and tennis.